2018
DOI: 10.5350/sleep.hypn.2017.19.0151
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality, Quality of Life and Insomnia Among Patients with Chronic Low Back Pain Compared to Normal Individuals

Abstract: Objective: Low back pain may affect various aspects of quality of life including sleep. There are some reports about prevalence of sleep disorders in patients with chronic low back pain. The present study was conducted to estimate sleep quality, quality of life, and insomnia in patients with chronic low back pain compared to age and sex matched control group. Methods: The present case-control study was performed on 140 persons (70 patients with chronic low back pain and 70 persons as control group). They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…However, it remains unclear whether baseline sleep quality/quantity can predict future LBP-related outcomes in individuals with CLBP. Our findings reveal a paucity of relevant research although many individuals with CLBP experience sleep disturbance 14,18,19,22. Our results also underscore the importance of determining the causal relations between sleep and pain/function in individuals with CLBP, which may improve the assessments and treatments of these individuals.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, it remains unclear whether baseline sleep quality/quantity can predict future LBP-related outcomes in individuals with CLBP. Our findings reveal a paucity of relevant research although many individuals with CLBP experience sleep disturbance 14,18,19,22. Our results also underscore the importance of determining the causal relations between sleep and pain/function in individuals with CLBP, which may improve the assessments and treatments of these individuals.…”
Section: Discussionmentioning
confidence: 76%
“…[14][15][16][17] Notably, patients with higher CLBP intensity showed significantly poorer selfreported sleep quality. [18][19][20][21] Studies also found that over 55% of patients with CLBP experienced sleep disturbance, 14,18,19,22 which might manifest as insufficient sleep, frequent awakening, a long sleep latency, difficulty in initiating or maintaining sleep, and/or waking up too early. 23,24 Although speculative, poor sleep may upregulate neuroinflammatory cytokines, which are thought to be related to the pathogenesis of CLBP and aggravation of pain sensitization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances for patients with rheumatic diseases include more treatment options with improved outcomes, yet there remains an unmet need with pain (1)(2)(3)(4). While pain is sometimes treated as a single dimension of a patient's health-related quality of life, many patients with chronic pain also experience associated symptoms in other dimensions including insomnia, anxiety, and depression (5)(6)(7)(8)(9)(10). Pain control is listed as one of the highest priorities by patients with rheumatoid arthritis (RA) (11); these patients often turn to alternative treatments to cope with pain, including acupuncture/acupressure, hypnosis, herbal therapies, and cannabis (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Важно отметить, что пациенты с ХНЛ имеют более низкое КЖ, худшее качество сна, чем пациенты без боли [2,15]. Влияние хронической боли на сон описывается как порочный круг с взаимным пагубным влиянием боли и нарушений сна [16].…”
Section: Abstract: Chronic Non-specific Low Back Pain; Chronic Insomnia; Complex Treatment; Sleep Hygiene; Cognitive-behavioral Therapy Ounclassified